Sulfonated PVA microspheres for drug delivery and simulated body fluid interaction - Verón, María Gisela; Álvarez Soria, Luciano; Pérez, Pablo Daniel; Prado, Miguel Oscar (Taylor & Francis, 2022)
Fil: Verón, María Gisela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte; Argentina